If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -77 = -9x + 113 Reorder the terms: -77 + X = -9x + 113 Reorder the terms: -77 + X = 113 + -9x Solving -77 + X = 113 + -9x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '77' to each side of the equation. -77 + 77 + X = 113 + 77 + -9x Combine like terms: -77 + 77 = 0 0 + X = 113 + 77 + -9x X = 113 + 77 + -9x Combine like terms: 113 + 77 = 190 X = 190 + -9x Simplifying X = 190 + -9x
| 15+3(4z-2b)=5b-2z | | S/107=100 | | 7(x+4)-3(x+6)=19 | | 2x+(3x-4)=(2x-3) | | 1+(1)(1)= | | (1)(1)+1= | | 9x-7=-3x+29 | | -1.4121-(1-2.4)= | | 4+(2)(3)= | | 4(2+3)= | | 7x-14=-3x+6 | | 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= | | 9x+7=-5+7x+16 | | -3(t+3)=15 | | 47-15=4(x-6) | | 70+5y-32=17y-11-5y | | 2+(-3)(4)= | | (36m-9mn=45n)/9 | | k^2+2k+-60=0 | | -4(p+5)= | | 4(2x+9)=-7x-24 | | 2(-3+4)= |